Portugal : from monarchy to pluralist democracy - Opello, Walter C. (Routledge, 2019)
Two basic processes--industrialization and the emergence of the nation-state--have marked the evolution of many modern societies, particularly in Western Europe. Industrialization broadened the class structure of societies. With the new classes came demands for political power and influence, demands that were vigorously resisted by the ruling monarchies and landowning aristocracies. And with these demands came upheaval and, eventually, new forms of democratic social and political organization. In Portugal's transition from absolutist monarchy to pluralist democracy can be found an example of these transformative processes at work. Yet the experience of this nation has been largely neglected in discussions of Western European politics. With Portugal: From Monarchy to Pluralist Democracy, Walter C. Opello, Jr., brings the transformation of Portugal into sharp focus and, in doing so, offers interesting insights into the problems of forming a democratic regime. This profile traces Portugal's transition to democracy within the broader context of its historical development as a nation-state, documenting the effects of absolutism, imperialism, centralization, class and regional cleavages, and late industrialization on the Portuguese people, their polity, economy, and society. Exploring the themes that have shaped the development of Portugal's democratic structures, Professor Opello also assesses the future viability of these structures in light of the country's nondemocratic legacies.